Gegen Qinlian Decoction Ameliorates Hyperuricemia-Induced Renal Tubular Injury via Blocking the Inflammatory Signaling Pathway - Wang, Xiao-Jun; Qi, Yi-Ding; Guan, Hao-Chen; Lin, Hua-Gang; He, Pei-Qing; Guan, Kang-Wei; Fu, Lei; Ye, Mao-Qing; Xiao, Jing; Wu, Tao (Frontiers in Pharmacology, 2021)
Background: Gegen Qinlian decoction (GGQLD) has been the typical traditional Chinese medicine (TCM) prescription documented in Shang Han Lun. GGQLD is utilized to manage the inflammatory symptoms of metabolic diseases, and to protect against renal function in China clinically. In this study, a hypothesis was proposed that the multi-target solution of GGQLD produced anti-inflammatory effects to ameliorate hyperuricemia (HUA). Methods: Altogether 30 primary HUA patients receiving GGQLD treatment (2 doses daily) for 4 weeks were selected; then, differences in uric acid (UA) levels as well as expression of peripheral blood mononuclear cells (PBMCs) and urinary exosomes before and after treatment were analyzed. The therapeutic targets for the active ingredients in GGQLD against HUA were confirmed through pharmacological sub-network analysis. Besides,the HUA rat model was established through oral gavage of potassium oxonate, and treated with oral administration of GGQLD. In addition, PTEC cells were stimulated by UA and intervened with GGQLD for 48 h. Then, RNA-seq, flow cytometry and confocal immunofluorescence microscopy were further conducted to characterize the differences in UA-mediated inflammation and apoptosis of human renal tubular epithelial cells pre and post administration of GGQLD. In addition, quantitative real-time PCR (qRT-PCR) was carried out to determine gene expression, whereas Western blotting assay was conducted to measure protein expression. Results: Our network analysis revealed that GGQLD acted via the anti-inflammatory and anti-apoptotic pathways in the treatment of HUA. Besides, NLPR3 expression significantly decreased in PBMCs and urinary exosomes of HUA patients after GGQLD treatment. In vivo, GGQLD treatment alleviated renal inflammation induced by HUA, which was associated with reduced expression of NLRP3 inflammasomes and apoptosis-related mRNAs. Moreover, GGQLD promoted renal UA excretion by inhibiting the activation of GSDMD-dependent pyroptosis induced by NLRP3 inflammasomes and reducing apoptosis via the mitochondrial apoptosis signaling pathway in vitro. Conclusion: This study indicates that GGQLD efficiently reduces inflammatory responses while promoting UA excretion in HUA. Our findings also provide compelling evidence supporting that GGQLD protects against the UA-mediated renal tubular epithelial cell inflammation through the mitochondrial apoptosis signaling pathways. Taken together, these findings have revealed a novel therapeutic method for the treatment of HUA.